THE INFLUENCE OF DIGITAL LIFESTYLE AND TRUST ON GENERATION Z CONSUMERS' PURCHASE DECISIONS IN BOGOR CITY ON SHOPEE E-COMMERCE - Rizky Sindhu Wardoyo; Kushardanta Susilabudi (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of digital lifestyle and trust on the purchasing decisions of Generation Z consumers in Bogor City on the e-commerce platform Shopee. The rapid development of digital technology has driven changes in consumer behavior, particularly among Generation Z, who demonstrate a high level of engagement in using the internet and digital applications for shopping activities. This research employs a quantitative approach, with data collected through questionnaires distributed to Generation Z respondents in Bogor City. The data were analyzed using multiple linear regression to examine the effect of independent variables on the dependent variable. The results indicate that digital lifestyle and trust have a positive and significant effect on purchasing decisions. These findings suggest that higher digital engagement and greater consumer trust increase the likelihood of making purchasing decisions. This study is expected to provide insights for e-commerce practitioners in understanding the behavior of Generation Z consumers.